The Ghawa Syndrome in Kuwaiti-Arabic Verbs - Taqi, Hanan A. (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
The “Ghawa Syndrome” is a well-known linguistic phenomenon in the Arabian Gulf. In this phenomenon, the first open syllabus of a word is re-syllabified. The current study investigates the occurrence of this linguistic feature in Kuwaiti verbs within the variation of accents in the speech of two ethnic groups (Najdis and Ajamis) and three generations. The ethnicity factor was believed to play a major role in the linguistic feature under investigation due to their varying social and economic status. 48 Kuwaiti individuals represented the two investigated ethnicities and three age groups (chosen according to relevant milestones in the history of Kuwait), and with an equal number of males and females participating in data collection. Three different techniques of data collection were utilized (picture-naming, map task, interview & questionnaires). The results reflected an increase in the use of the Ghawa Syndrome across generations in the Ajami group, while the Najdi dialect was rather stable. This linguistic familiarity seems to affect the two ethnicities, bringing them closer to each other.